Effect of free will on the creation of new impacts on the long-term temporary marriage - SHAFIEI FINI, H; MAHDI, R (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The principle of free will stipulates that the contract, in terms of ordering the legal consequences and determining the type and nature of the agreement between the parties, should not conflict with certain rules. Given that the overwhelming majority of jurists and lawyers have considered the principle of free will as the origin of Article 10 of the Civil Code, as well as the rule of law of the subsidiary, but there is no consensus among them on the meanings and definitions of the principle of free will, in this paper, the impact of free will on the creation of new impacts on the long-term temporary marriage contract is examined.